2006
DOI: 10.2223/jped.1461
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of allergic rhinitis among adolescents from Distrito Federal, Brazil: comparison between ISAAC phases I and III

Abstract: Objectives: To determine the prevalence of allergic rhinitis in a random group of schoolchildren aged 13 to 14 years in Brasilia, Brazil, to evaluate tendencies over 6 years and to compare prevalence rates among different socioeconomic groups.Methods: Two cross-sectional studies were undertaken 6 years apart, using the ISAAC (phases I and II) written questionnaire. Thirtynine schools were chosen at random from eight administrative regions in Brasilia, and were classified into three groups according to the soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
11
0
1

Year Published

2008
2008
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 14 publications
(8 reference statements)
8
11
0
1
Order By: Relevance
“…However, in this study we found a higher frequency of rhinoconjunctivitis in girls than in boys, both in childhood and adolescence. Our results are in line with those from the German study that compared ISAAC phases I (1995) and III (2000), which found that girls had a higher prevalence of rhinoconjunctivitis compared to boys in both periods, and increasing trends in the prevalence for girls in phase-III [27][28][29][30][31][32]. The same was found in Estonia [35], Finland [36] and United Kingdom [37].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, in this study we found a higher frequency of rhinoconjunctivitis in girls than in boys, both in childhood and adolescence. Our results are in line with those from the German study that compared ISAAC phases I (1995) and III (2000), which found that girls had a higher prevalence of rhinoconjunctivitis compared to boys in both periods, and increasing trends in the prevalence for girls in phase-III [27][28][29][30][31][32]. The same was found in Estonia [35], Finland [36] and United Kingdom [37].…”
Section: Discussionsupporting
confidence: 91%
“…However, the increase in prevalence was more common in the group aged 6-7 years than in the group of adolescents aged 13-14 years. Although the centers report a wide variety of results for both age groups, most of the centers reported an increase in the prevalence of the three allergic diseases (asthma, allergic rhinitis, atopic dermatitis) as reported in Hong Kong [27], Turkey [28], and the comparative studies between phase I and III in Germany [29], Brazil [30], and Poland [31]; while others reported a decrease [5].…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Sherrill et al 34 report prevalences of AR of between 20% and 29% in this age group; however, their definition of AR was only based on current symptoms or medication and not on physician-diagnosed AR with current symptoms and is therefore less specific than ours.…”
Section: Discussionmentioning
confidence: 55%
“…The risk factors indicated in our study are in accordance with those of other studies. 11,31,35,36 However, thus far, none of these studies have used the information for individual prediction of disease course.…”
Section: Discussionmentioning
confidence: 99%
“…Using the data from the International Study of Asthma and Allergies in Childhood (ISAAC), researchers in Cape Town, South Africa, found a positive association between higher SES and the prevalence of allergic rhinitis (38). An ISAAC study in Brazil also found a higher prevalence of physician-diagnosed rhinitis among those with higher versus lower SES (defined as ''purchasing power'') (39). In a population-based study of 1.2 million Swedish males (ages 17 to 20 yr) conducted over three decades, low SES was associated with reduced odds of allergic rhinitis among those born in the earliest cohorts (OR, 0.84; 95% CI, 0.82-0.85).…”
Section: Discussionmentioning
confidence: 99%